2021
DOI: 10.3390/s21103328
|View full text |Cite
|
Sign up to set email alerts
|

Flow Control in Porous Media: From Numerical Analysis to Quantitative μPAD for Ionic Strength Measurements

Abstract: Microfluidic paper-based analytical devices (µPADs) are a promising technology to enable accurate and quantitative in situ assays. Paper’s inherent hydrophilicity drives the fluids without the need for external pressure sources. However, controlling the flow in the porous medium has remained a challenge. This study addresses this problem from the nature of the paper substrate and its design. A computational fluid dynamic model has been developed, which couples the characteristics of the porous media (fiber len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Depending on the needs, fluid flow can be controlled by changing nature of the paper substrate and its design by using 2D or 3D fabrication techniques. 25,26 A small change in the rate of fluid flow can lead to erroneous results in these devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the needs, fluid flow can be controlled by changing nature of the paper substrate and its design by using 2D or 3D fabrication techniques. 25,26 A small change in the rate of fluid flow can lead to erroneous results in these devices.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the needs, fluid flow can be controlled by changing nature of the paper substrate and its design by using 2D or 3D fabrication techniques. 25,26 A small change in the rate of fluid flow can lead to erroneous results in these devices. Over the past few years, there have been studies of viscous barriers of various concentrations embedded with a paper channel to control its flow velocity by varying the pore size.…”
Section: Introductionmentioning
confidence: 99%
“…µPADs can be designed as an important component of instrument‐free, portable detectors. Due to their unique properties, µPADs are ideal for large‐scale point‐of‐care (POC) applications (Krishnan & Syed, 2022) and fulfilled all the criteria of ASSURED law (including affordable, sensitive, specific, user‐friendly, rapid and robust, equipment‐free, and deliverable to end‐customers) (Mehrdel et al, 2021; Puiu & Bala, 2020) and provides sustainable solutions (Kishnani et al, 2022). These characteristics compensate for the common limitations of conventional devices, allowing for the development of ideal POC devices for low‐resource settings (Trinh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…papers. Paper C [128] showed that characteristics such as channel width, inlet branches length and the paper strips length, were vital and therefore equal in all the developed models.…”
Section: Inlet Geometry Analysis In µPad Applicationsmentioning
confidence: 99%
“…In the µPAD development study (Paper C [128]) a similar strategy to the previous assay for detection and quantification of ionic concentration was taken. The used reagents and materials are described as follows.…”
Section: µPad Assaymentioning
confidence: 99%